Eksplorasi Persepsi Ibu tentang Pendidikan Seks untuk Anak - Shofwatun Amaliyah; Fathul Lubabin Nuqul (Fakultas Psikologi, Universitas Islam Negeri (UIN) Sunan Gunung Djati Bandung, 2017)
Sex education is the provision of information about sex that aims to reduce the potential risk of sexual behavior. This effort is still taboo in the community, so parents feel hesitant to provide teaching about sex to children. The purpose of this study is to determine the perception of parents to sex education provided to children from an early age. This research was conducted in Jambesari village, Poncokusumo, Malang by using phenomenology approach and involving 5 mothers. The results show that parents perceive sex education as taboo, vulgar and inappropriate to convey to children, thus affecting the involvement and form of education provided by parents to children. The results also show that the need for the competence of sexual education is important to be done by parents.